(untitled) (AYUSHDHARA, 2021)
Ayurveda has emerged and developed as a holistic system of treatment. It has a great treasure of knowledge of natural drugs (Plant, Animal and Mineral originated) that has been in use since long to maintain the health and mitigate the adverse situation in the body during diseases. Even though Ayurveda is a medical science, other various disciplines related to medicine are also described in detail in it; Pharmaceutical science is one of them. Ayurvedic pharmaceutics is completely scientific and it has arisen from centuries of experiences. Vast literature is available on different issues of pharmaceutics in Ayurveda such as collection of raw material from their natural sources; identification & their validation; various purification, manufacturing and analytical methods; shelf life of drug & storage methods etc. All these relevant issues have been described in a very scientific manner, but recent developments of pharmaceutics need to be incorporated in existing science for their acceptance globally. Gomutra haritaki is a medicine that has Gomutra (Animal product) and Haritaki (Plant product) as ingredients and both have immense biochemical properties and prescribed in various ailments. In Ayurvedic text Gomutra haritaki has been described in Pandu roga (Anemia), Mukha roga (Mouth diseases) and Arsha (Piles). Through this article, an attempt has been made to collect the all related classical references, and generate the standard operative procedures for manufacturing. Gomutra haritaki was prepared as per description available in Vrihat nighantu ratnakar. It was yellowish brown in color and there was an intense smell of cow urine. Organoleptic and physiochemical characterization was evaluated through validated standardization procedures.